2020
DOI: 10.21203/rs.3.rs-71500/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Circular RNA circ-LRIG3 Facilitates the Malignant Progression of Hepatocellular Carcinoma by Modulating the EZH2/STAT3 Signaling

Abstract: Background: Circular RNA (circRNA) is emerging as an important player in human diseases, especially cancer. In our previous study, we identified a series of deregulated circRNAs in hepatocellular carcinoma (HCC) by performing circRNA microarray expression profile. Here, we aimed to explore the role of circ-LRIG3 (hsa_circ_0027345) in HCC.Methods: qRT-PCR and western blot were used to asses gene and protein expression, respectively. CCK-8, EdU and Transwell assays were used to detect cell proliferation, migrati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…23,24 Many molecular functions are performed by cir-cRNAs to implement their cellular effects, such as interacting with different proteins to form specific RNPs and influence their intrinsic function. [25][26][27] In our study, we present evidence that PLCE1 mRNA production is negatively controlled by its circRNA via suppression of pre-PLCE1 splicing. One of our main findings is that circPLCE1 directly binds to the SRSF2 protein and suppresses the spliceosome assembly on nascent pre-PLCE1 to catalyse intron removal before the completion of transcription (Figure 6F).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…23,24 Many molecular functions are performed by cir-cRNAs to implement their cellular effects, such as interacting with different proteins to form specific RNPs and influence their intrinsic function. [25][26][27] In our study, we present evidence that PLCE1 mRNA production is negatively controlled by its circRNA via suppression of pre-PLCE1 splicing. One of our main findings is that circPLCE1 directly binds to the SRSF2 protein and suppresses the spliceosome assembly on nascent pre-PLCE1 to catalyse intron removal before the completion of transcription (Figure 6F).…”
Section: Discussionmentioning
confidence: 56%
“…Recently, evidence has accumulated that circRNAs are frequently dysregulated in human cancer and affect tumorigenesis, invasion and metastasis 23,24 . Many molecular functions are performed by circRNAs to implement their cellular effects, such as interacting with different proteins to form specific RNPs and influence their intrinsic function 25‐27 . In our study, we present evidence that PLCE1 mRNA production is negatively controlled by its circRNA via suppression of pre‐PLCE1 splicing.…”
Section: Discussionmentioning
confidence: 57%
“…In addition to dominant localization in the cytoplasm, some circRNAs are located in the nucleus. For example, circLRIG3 preferentially located in the nucleus and interacts with both EZH2 and STAT3 in hepatocellular carcinoma to form a circRNA-protein complex, facilitating EZH2-induced activation of STAT3 signaling and promoted HCC cell proliferation and metastasis [57]. CircURI1 was reported to preferentially locate in the nucleus in both AGS and SGC7901 cells.…”
Section: Discussionmentioning
confidence: 99%
“…For positive regulation, RNA binding proteins (RBPs) promote circularization by reducing spatial proximity as most of them bind to their binding sites in flanking introns (Ashwal-Fluss et al 2014;Conn et al 2015;Dai et al 2018). Besides, the upstream promoter of the circRNA is activated under some circumstances, which also contributes to the formation of the circRNA (Zhao et al 2020b;Wang et al 2018;Sun et al 2020a). However, it's reported that circularization can be promoted by most RBPs except DHX9, which inhibits the production of circDLC1 as it can bind to the flanking reverse complementary sequence of circDLC1 and inhibit the pairing of these sequences .…”
Section: Regulation Of Circrna Biogenesismentioning
confidence: 99%
“…For example, circLRIG3 physically interacts with EZH2 and STAT3 and acts as a scaffold to increase EZH2-induced STAT3 methylation and subsequent phosphorylation. In turn, activated STAT3 directly binds to the circLRIG3 promoter region, which enhances the circLRIG3 transcription, and at last, forms a positive regulatory circuit that improves hepatocellular carcinoma (HCC) processes (Sun et al 2020a). Another example is circNDUFB2 that binds to the IGF2BPs KH domain and acts as a stent to enhance the interaction between TRIM25 and IGF2BPS, eventually expediting TRIM25-mediated IGF2BPS ubiquitination and degradation (Li et al 2021a).…”
Section: Scaffoldmentioning
confidence: 99%